Management of neck metastases of unknown primary origin united in two European centers - Straetmans, Jos; Vent, Julia (European archives of oto-rhino-laryngology and head & neck, 2015)
Combined analysis of diagnostic and therapeutic management of neck metastases of carcinoma of unknown primary origin (‘true CUP’) in two European tertiary referral centers (University Medical Centers of Maastricht, NL and Cologne, D) to contribute to the ongoing discussion on management in CUP. Retrospective analysis of 29 (Maastricht) and 22 (Cologne) true cervical CUP syndrome patients (squamous cell carcinoma). The diagnostic and therapeutic approaches were correlated with clinical follow-up data and HPV status. In total, 48 out of 51 true CUP patients received postsurgical adjuvant radiotherapy. In eight patients from Cologne, this was combined with concomitant platin-based chemotherapy. Neither in Cologne nor in Maastricht, radiotherapy of the pharyngeal mucosa was commonly performed (n = 6, 12.5 %) The percentage of patients who were irradiated ipsilaterally or bilaterally did not differ between both institutes (N = 21/27 in Maastricht vs. 11/21 in Cologne), nor did the 5-year overall survival differ significantly. Oncogenic HPV was only found in 4 out of 51 CUPs (7, 8 %). Therefore, no relation with overall and recurrence-free survival could be detected. No occult primary tumors were revealed during follow-up despite de-escalation of therapy by abandoning irradiation of the pharyngeal mucosa in both institutes. There were no significant differences between ipsilateral and bilaterally irradiated patients regarding overall and recurrence-free survival. The occurrence of distant metastases was more often noticed in ipsilaterally treated patients as compared to bilaterally radiated patients (8 vs. 2, p = 0.099). Those patients all had been classified N2b or higher. International guidelines still are not unified and there is an urgent need for a consented therapeutic regimen. Comparison of two international strategies on the management of CUP patients is presented and further research is recommended regarding the role of radiotherapy of the pharyngeal axis, the value of unilateral and bilateral radiotherapy and the role of concomitant or induction chemotherapy in CUP patients, particularly in N2b or higher-staged neck disease. The prevalence and role of HPV in true CUP after thorough diagnostic work-up seem limited in our case series, particularly when compared to the role in oropharyngeal carcinomas.
Gesehen am 19.10.2017